Oil pollution in the straits of Malacca, Malaysia: Application of molecular markers for source identification - Zakaria, Mohamad Pauzi; Horinouchi, Ai; Tsutsumi, Shinobu; Takada, Hideshige; Tanabe, Shinsuke; Ismail, Ahmad (American Chemical Society (ACS), 2000)
The Straits of Malacca is one of the world's busiest supertanker routes, and tanker-derived oil spills occur frequently. In addition, domestic oil spills have been increasing due to growing industrialization of Malaysia. The deter mination of the exact source of the spills is critically important. This paper examines the utility of biomarker compounds, triterpanes, to identify the source of the oil spills. Middle East crude oils (MECO), South East Asian crude oils (SEACO), tar-balls, sediments, and mussels were analyzed. The most distinctive compositional features for the crude oils are that 17α, 21β(H)C29 norhopane and C31−C35 homohopanes, especially C35 homohopanes, are depleted in SEACO. These remarkably different hopane compositions can be explained by the fact that MECO and SEACO are derived from carbonate (marine) and lacustrine/deltaic shale (nonmarine) source rocks, respectively. Two of the eight tar-balls samples collected on the coast of Peninsular Malaysia were identified to be derived from Middle East petroleum based on their biomarker signatures. The results of oleanane analyses imply that a low concentration of oleanane does not always indicate a Middle East petroleum contribution although at high concentration oleanane can be a useful biomarker for South East Asian oil sources. Application of the source-identifier to sediment and mussel samples showed the Middle East oil signature. One possible explanation is that Middle East oil is used in formulating Malaysian lubricating oils which are the source of oil found in sediment and mussel samples. This is consistent with the analytical results for the lubricating oil used in Malaysia and the street dust samples.